Integrasi Nilai-Nilai Islam dalam Pembelajaran IPS di MI - Risma Dwi Arisona (Proceedings of Annual Conference for Muslim Scholars, 2017)
Basic education is still to be independent and stand on their own. The circumstances that lead to action learning and learning management are not integrated. Developing educational materials in MI is also not show good results. This condition is due to be delivered learning materials and curriculum are still partial and not yet integrating throughout the content value of the other materials, especially religion. IPS is a subject that comes from social life that were selected by using the concepts of social science that is used for the sake of learning. To that end, in a social studies lesson in MI must be integrated with the values of Islam, so the IPS learning objectives can be achieved. The integration can be done by first sorting the basic competence between IPS and PAI which can be integrated in the learning process. So that the learning can be good result. Implementation of this learning has many advantages. However, in the implementation were also encountered weaknessKeywords: integration, Islamic values, social science